A dehydrin-dehydrin interaction: the case of SK3 from Opuntia streptacantha - Itzell eHernandez; David eMartynowicz; Aida eRodriguez; Maria Beatriz Pérez-Morales; Steffen P Graether; Juan Francisco Jimenez Bremont (Frontiers in Plant Science, 2014)
Dehydrins belongs to a large group of highly hydrophilic proteins known as Late Embryogenesis Abundant (LEA) proteins. It is well know that dehydrins are intrinsically disordered plant proteins that accumulate during the late stages of embryogenesis and in response to abiotic stresses; however, the molecular mechanisms by which their functions are carried out are still unclear. We have previously reported that transgenic Arabidopsis plants overexpressing an Opuntia streptacantha SK3 dehydrin (OpsDHN1) show enhanced tolerance to freezing stress. Herein, we show using a split-ubiquitin yeast two-hybrid system that OpsDHN1 dimerizes. We found that the deletion of regions containing K-segments and the histidine-rich region in the OpsDHN1 protein affects dimer formation. Not surprisingly, in silico protein sequence analysis suggests that OpsDHN1 is an intrinsically disordered protein, an observation that was confirmed by circular dichroism and gel filtration of the recombinantly expressed protein. The addition of zinc triggered the association of recombinantly expressed OpsDHN1 protein, likely through its histidine-rich motif. These data brings new insights about the molecular mechanism of the OpsDHN1 SK3-dehydrin